GE_GERICHTE P/12041/2019 vom 8. November 2023 - GE Cour de justice (2023)
HOMICIDE PAR NÉGLIGENCE;DISPOSITIONS PÉNALES DE LA LCR;SURSIS À L'EXÉCUTION DE LA PEINE;TORT MORAL;MORT | CP.117; CP.12.al3; CP.40; CP.42; CO.49; CO.47; CP.47; CPP.433